Analisis Sumber dan Penggunaan Modal Kerja pada PT. BPR Anugerahdharma Yuwana Cabang Ambulu Kabupaten Jember - Tohari, Nursyamsida; Fitriana, Alya (ACCOUNT (Journal of Accounting and Finance), 2024)
This research aims to analyze the sources and use of working capital at PT. BPR Anugerahdharma Yuwana Ambulu Branch, Jember Regency 2021 – 2022. The data used in this research are qualitative data and quantitative data from PT. BPR Anugerahdharma Yuwana Ambulu Branch, Jember Regency. The analytical method used is a quantitative descriptive method, namely by analyzing the balance sheet financial report of PT. BPR Anugerahdharma Yuwana Ambulu Branch, Jember Regency in 2021 – 2022 to find out the source and use of working capital. From the results of the analysis it was found that working capital at PT. BPR Anugerahdharma Yuwana Ambulu Branch, Jember Regency experienced an increase of Rp. 158,850,227. Meanwhile, from the report on sources and use of working capital, it is known that the source of working capital is greater than the use of working capital so that the financial management performance of PT. BPR Anugerahdharma Yuwana Ambulu Branch, Jember Regency is getting better.